Pengaruh Harga dan Promosi terhadap Impulse Buying pada Produk Online Menurut Ekonomi Syariah - Mufti Hasan Alfani (COSTING : Journal of Economic, Business and Accounting, 2020)
Advances in internet technology currently make online shopping systems become instant and very popular. This study aims to determine the analysis of the Effect of Prices and Promotions on Impulse Buying in Online Products According to Islamic Economics. Where the results of the pre-survey to students of the Faculty of Islam about Online products on the influence of prices and promotions on impulsive purchases. The sampling technique in this study used a purposive sampling technique by taking a sample of 100 respondents. This research uses a quantitative approach with the method of data analysis of Multiple Linear Regression with the help of the SPSS Program Application Version 21.0 for Windows. The results of this study indicate that there is an effect of Price and Promotion on the performance of Impulse Buying on online products. As well as the effect of Price and Promotion on Impulse Buying in the Sharia Economy perspective on the influence of consumer behavior on purchasing decisions via mobile phones they apply concepts that are in accordance with the teachings of Islam that is not beyond the limits of reasonableness, and positively. Because the Al-Qur'an forbids excessive spending on wealth solely following the passions, while on the other hand also condemns the act of distancing yourself from the pleasure of enjoying things that are good and lawful in life.Keywords: Price, Promotion, Impulse Buying, Online Products, Sharia Economy.